A study on the influencing factors and response strategies for young teachers from Taiwan to teach in universities in China: a push-pull-mooring model perspective - Wang, Li; Miao, Cong-Jin; Ye, Jian-Hong; Huang, Xin; Nong, Liying; Nong, Weiguaju (Frontiers in Psychology, 2023)
Introduction A growing number of Taiwanese teachers are choosing to teach at universities in mainland China, but their jobs are not always stable. Therefore, this study aims to investigate the factors infuencing young teachers from Taiwan to teach in universities in China. Methods Twenty-seven young teachers from Taiwan with master’s or doctoral degrees who were willing to apply to work at universities in China and who were already teaching in China were invited to conduct in-depth interviews to collect research data.The interview data were coded and analyzed according to the Push-Pull-Mooring (PPM) Model. Results and discussion The results showed that the understanding of mainland Chinese universities among young Taiwanese teachers is not entirely consistent. Taiwanese teachers who previously studied in mainland China have a more comprehensive understanding of mainland Chinese universities, and some teachers have gained a superfcial understanding through academic exchanges between the two sides and information shared by friends.However,still,7% of the teachers have no understanding at all. Most young Taiwanese teachers indicate that they do not understand the talent recruitment policies of mainland Chinese universities. The push factors that infuence young teachers from Taiwan to teach at mainland universities are: Oversupply of teachers in Taiwan, poor environment for higher education in Taiwan, poor articulation of the cross-strait academic system, and four aspects of teacher retirement and re-employment in Taiwan. The pull factors are: Benefcial policies, salary, living environment, educational advantages and cultural dissemination in 5 areas. Mooring factors are divided into 3 aspects: personal factors, environmental factors and social factors.